DESAIN SISTEM ABSENSI KARYAWAN DENGAN RADIO FREQUENCY IDENTIFICATION BERBASIS WEB - Reva Ragam Santika; Yudi Wiharto; Ari Irawan (Universitas Tridharma, 2021)
Attendance is a mandatory procedure that is always carried out by every employee in his institution including Cv Wiragati Media. Problems have been found with the current attendance system, the attendance process at Cv Wiragati Media is still using a manual system using a clock check tool where there is still a gap for employee delays in coming to the office, resulting in frequent employees manipulating their attendance data. To improve the attendance system, in this case, it uses the NodeMcu ESP8266 microcontroller where this microcontroller is a monitoring and controlling system and the RC522 RFID Reader as a module for reading RFID cards. Where later each employee only needs to attach the RFID card to the RC522 RFID Reader Module which has been given and registered by the institution for real time employee attendance (arrival and return) processes. With this system, the institution can see the attendance data of all employees in real time which is web-based and makes it easier for the admin or operator who is in charge of recapitulating employee attendance. Keywords— attendance, employees, microcontroller, RFID